Sagot :
Réponse :
bonjour!
Explications étape par étape :
D = (+24) ÷ (-6)-(-6)
=-4+6
=2
E =(-15)-(+18)÷(+3)
=-15 -6
=-21
G=-3+3×(-12)-(-15)÷3
= -3 -36 +5
=-34
F = (-6)+(+3) × (-9)
=-6 + (-27)
=-6-27
=-33
H = -6 +25 ÷ [2×(-4)-(9-3×4)]
=-6+25 / [-8 -(9-12)]
=-6 +25 / -5
=-6 +(-5)
=-11
Bonjour,
Priorités de calculs : parenthèses // x et : // + et -
+ et + = +
+ et - = -
- et - = +
D = (+24) ÷ (-6)-(-6)
D = - 4 + 6
D = 2
E =(-15)-(+18)÷(+3)
E = - 15 - (+6)
E = - 15 - 6
E = - 21
G=-3+3×(-12)-(-15)÷3
G = - 3 - 36 - (-5)
G = - 3 - 36 + 5
G = - 34
F = (-6)+(+3) × (-9)
F = - 6 - 27
F = - 33
H = -6 +25 ÷ [2×(-4)-(9-3×4)]
H = - 6 + 25 : (-8 - (9 -12))
H = - 6 + 25 : (-8 - ( -3))
H = - 6 + 25 : (-8 + 3)
H = - 6 + 25 : (-5)
H = - 6 - 5
H = - 11
Bonne journée.